2008
DOI: 10.1016/j.contraception.2007.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Safety and tolerability of depot medroxyprogesterone acetate among HIV-infected women on antiretroviral therapy: ACTG A5093

Abstract: Background-Concomitant use of antiretrovirals (ARV) and hormonal contraceptives may change the metabolism of each and the resulting safety profiles. We evaluated the safety and tolerability of depot medroxyprogesterone acetate (DMPA) among women on ARV.Study Design-HIV-infected women on selected ARV regimens or no ARV were administered DMPA 150 mg intramuscularly and evaluated for 12 weeks for adverse events, changes in CD4+ count and HIV RNA levels, and ovulation.Results-Seventy evaluable subjects were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 24 publications
1
36
0
Order By: Relevance
“…Discontinuation for side-effects, particularly those associated with bleeding and weight changes, was also common to Kenya and South Africa sites and similar to that reported among populations in the United States and Zambia [26,69]. However, HIV likely factored into intolerance of oligo/amenorrhea and weight loss due to fears of deteriorating health and imminent AIDS, particularly in Kenya and South Africa where ART availability is relatively recent.…”
Section: Discussionmentioning
confidence: 52%
“…Discontinuation for side-effects, particularly those associated with bleeding and weight changes, was also common to Kenya and South Africa sites and similar to that reported among populations in the United States and Zambia [26,69]. However, HIV likely factored into intolerance of oligo/amenorrhea and weight loss due to fears of deteriorating health and imminent AIDS, particularly in Kenya and South Africa where ART availability is relatively recent.…”
Section: Discussionmentioning
confidence: 52%
“…Cohn et al 29 found no significant changes in medroxyprogesterone acetate levels among 54 HIV-infected women using ARV regimens that included nevirapine, efavirenz, or the PI nelfinavir compared with those in 16 controls using other ARV regimens or on no ARVs. DMPA was well tolerated, no women had evidence of ovulation during the 12-week study, and minor adverse effects observed were similar to those seen in HIV-uninfected women, 30 Although this study demonstrated the safety and efficacy of a PI-based regimen (eg, nelfinavir) with injectable progestins, it did not evaluate ARV regimens that included RTV.…”
Section: Discussionmentioning
confidence: 85%
“…The literature regarding EFV is more mixed. Studies have found no effect of EFV on progesterone levels when using DMPA [8,10,16], but significantly lower progesterone levels among implant users [17–19,15], along with contraceptive failure rates up to 15% among levonorgestrel implant users [2022]. Evidence regarding EFV and OCs is very limited, suggesting lower progesterone levels but not necessarily increased ovulation on EFV [13,23,24].…”
Section: Discussionmentioning
confidence: 99%